LYMPHOGENIC METASTASIS IN LUMINAL-TYPE A BREASR CANCER - M. V. Zavjalova; N. S. Telegina; S. V. Vtorushin; V. M. Perelmute; E. M. Slonimskaya; E. V. Denisov; N. V. Cherdyntseva; S. V. Patalyak; N. A. Skryabin; K. Yu. Khristenko (Сибирский онкологический журнал, 2016)
The present study has found significant heterogeneity of luminal A breast cancer group, which is manifested by differences in relationship between the frequency of lymphogenic metastasis and morphologic and molecular-biological parameters of the primary tumor. The frequency of regional metastases has appeared to relate to the presence of microalveolar structures in infiltrating component of invasive ductal breast cancer and to its phenotypic variety only in menopausal patients. It can be evidence of differences in tumor  pathogenesis in patients with different state of menstrual function even within one molecular-genetic tumor group. It is important to emphasize that the different variantsof clinical behavior of luminal A breast cancer are associated with morphological parameters of the tumor, allowing one to easily obtain the additional information during histological examination of bioptic material for predicting clinical course of luminal-type A breast cancer.